2022
DOI: 10.1186/s40352-022-00198-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of an Adverse Childhood Experiences (ACEs) measurement tool: an equitable assessment or reinforcing biases?

Abstract: Background Utilizing Adverse Childhood Experiences (ACEs) measurement scales to assess youths’ adversities has expanded exponentially in health and justice studies. However, most of the ACEs assessment scales have yet to meet critical psychometric standards, especially for key demographic and minority groups. It is critical that any assessment or screening tool is not reinforcing bias, warranting the need for validating ACEs tools that are equitable, reliable and accurate. The current study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Specifically, Ford et al (2014) found that measurement invariance was supported across age and gender identity groups when testing a three-factor latent model of ACEs. Mei et al (2022) replicated this three-factor model across age, race, sex, socioeconomic status, gender identity, and sexual orientation. However, both studies were conducted among adults, resulting in meaningful opportunities to continue exploring measurement invariance related to ACE items among children and youth (Negriff et al, 2022).…”
Section: Considerations Of Measurement Invariancementioning
confidence: 57%
See 1 more Smart Citation
“…Specifically, Ford et al (2014) found that measurement invariance was supported across age and gender identity groups when testing a three-factor latent model of ACEs. Mei et al (2022) replicated this three-factor model across age, race, sex, socioeconomic status, gender identity, and sexual orientation. However, both studies were conducted among adults, resulting in meaningful opportunities to continue exploring measurement invariance related to ACE items among children and youth (Negriff et al, 2022).…”
Section: Considerations Of Measurement Invariancementioning
confidence: 57%
“…Mei et al. (2022) replicated this three‐factor model across age, race, sex, socioeconomic status, gender identity, and sexual orientation. However, both studies were conducted among adults, resulting in meaningful opportunities to continue exploring measurement invariance related to ACE items among children and youth (Negriff et al., 2022).…”
Section: Background Of Acesmentioning
confidence: 86%
“…However, our measure of low household income was affected by around one in three survey participants either not knowing (n=391) or preferring not to report (n=215) their annual household income; consequently, these individuals were categorised in the comparator group for individuals who disclosed an annual income of <£20 000. ACEs were measured retrospectively with a tool that has been widely used in both general and high-risk populations and for which acceptable psychometric properties have been shown in various population groups 41–44. The short ACE tool is restricted by the limited range of ACEs it covers and here we used the initial version of the tool which did not include physical and emotional neglect.…”
Section: Discussionmentioning
confidence: 99%
“…The measure is commonly used to identify health inequities due to ACE [ 2 , 7 ]. However, it has not been evaluated specifically within Black SMM, nor among any transgender women (TW) [ 8 , 9 ]. There are reasons to believe existing ACE measurements might be inadequate for Black SMMs and may not capture community context, where general racial inequities in ACE exist due to higher incarceration, higher rates of parental absence and separation, other institutional disparities [ 5 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, past studies using population-based data from the BRFSS usually only have a small number of Black SGM participants, limiting the potential generalizability and inference [ 9 ]. These surveys typically used a single item gender identity question, which is deemed inadequate to identify transgender individuals [ 12 ].…”
Section: Introductionmentioning
confidence: 99%